Mental illness stigma and disclosure in college students. (3rd May 2016) - Corrigan, Patrick W.; Kosyluk, Kristin A.; Markowitz, Fred; Brown, Robyn Lewis; Conlon, Bridget; Rees, Jo; Rosenberg, Jessica; Ellefson, Sarah; Al-Khouja, Maya
Abstract: Objective : The aim of this study was to investigate the relationship between mental illness identity, shame, secrecy, public stigma, and disclosure amongst college students. Participants included 1393 college students from five postsecondary institutions. Methods : Structural equation modeling was used to examine two path models predicting disclosure and desire to join a program aiding with disclosure. Results : Variables found to be significant in predicting disclosure included mental illness identity and public stigma. In turn, desire for disclosure predicted desire to join a program aiding in disclosure. Gender and race/ethnic differences were observed, with men and Whites more likely to want to disclose a mental illness or join a program aiding with disclosure compared with women and non-Whites, respectively. Conclusions : These findings suggest that some college students may find programs aiding in disclosure useful in assisting them to achieve their desire to be "out" with their mental illness.